2012
DOI: 10.3390/rs4123813
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Distinction of Two Caribbean Shallow-Water Corals Based on Their Pigments and Corresponding Reflectance

Abstract: Abstract:The coloration of tropical reef corals is mainly due to their association with photosynthetic dinoflagellates commonly known as zooxanthellae. Combining High Performance Liquid Chromatography (HPLC), spectroscopy and derivative analysis we provide a novel approach to discriminate between the Caribbean shallow-water corals Acropora cervicornis and Porites porites based on their associated pigments. To the best of our knowledge, this is the first time that the total array of pigments found within the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The relatively low correlation between ΣR and symbiont density in Inshore (S. trenchii) P. rugosa may be the result of significantly different photoacclimation and pigment status of the symbiont cells. Previous research found a strong inverse relation with high predictability (R 2 ě 0.80) for ΣR and total tissue pigment concentration [12,60]. Integrated reflectance shows potential as a remote sensing tool for rough estimation of symbiont cell densities, however preceding parameterizations will be required for symbiont and coral species, as illustrated here by the higher overall reflectance of P. rugosa compared to C. serailia and corresponding distinct relationships between ΣR and symbiont density.…”
Section: Spectral Variability With Symbiont Concentrationmentioning
confidence: 78%
See 4 more Smart Citations
“…The relatively low correlation between ΣR and symbiont density in Inshore (S. trenchii) P. rugosa may be the result of significantly different photoacclimation and pigment status of the symbiont cells. Previous research found a strong inverse relation with high predictability (R 2 ě 0.80) for ΣR and total tissue pigment concentration [12,60]. Integrated reflectance shows potential as a remote sensing tool for rough estimation of symbiont cell densities, however preceding parameterizations will be required for symbiont and coral species, as illustrated here by the higher overall reflectance of P. rugosa compared to C. serailia and corresponding distinct relationships between ΣR and symbiont density.…”
Section: Spectral Variability With Symbiont Concentrationmentioning
confidence: 78%
“…Torres-Pérez et al [12] were able to discern variability in the magnitude of near infrared reflectance related to different species of coral. Our analysis however was not able to reliably estimate the reflectance beyond 700 nm because of the experimental setup where the near infrared was highly absorbed due to water molecules.…”
Section: Reflectance Of Different Coral/symbiont Systemsmentioning
confidence: 99%
See 3 more Smart Citations